The role of metals in mammalian olfaction of low molecular weight organosulfur compounds. Issue 5 (4th May 2017) - Block, Eric; Batista, Victor S.; Matsunami, Hiroaki; Zhuang, Hanyi; Ahmed, Lucky
Abstract : We highlight the role that copper and other metals play in mammalian olfaction of low molecular weight organosulfur compounds from both natural and non-natural sources. Abstract : Covering: up to the end of 2017 While suggestions concerning the possible role of metals in olfaction and taste date back 50 years, only recently has it been possible to confirm these proposals with experiments involving individual olfactory receptors (ORs). A detailed discussion of recent experimental results demonstrating the key role of metals in enhancing the response of human and other vertebrate ORs to specific odorants is presented against the backdrop of our knowledge of how the sense of smell functions both at the molecular and whole animal levels. This review emphasizes the role of metals in the detection of low molecular weight thiols, sulfides, and other organosulfur compounds, including those found in strong-smelling animal excretions and plant volatiles, and those used in gas odorization. Alternative theories of olfaction are described, with evidence favoring the modified "shape" theory. The use of quantum mechanical/molecular modeling (QM/MM), site-directed mutagenesis and saturation-transfer-difference (STD) NMR is discussed, providing support for biological studies of mouse and human receptors, MOR244-3 and OR OR2T11, respectively. Copper is bound at the active site of MOR244-3 by cysteine and histidine, while cysteine, histidine and methionine are involved with OR2T11. The binding pockets of these two receptors are found in different locations in the three-dimensional seven transmembrane models. Another recently deorphaned human olfactory receptor, OR2M3, highly selective for a thiol from onions, and a broadly-tuned thiol receptor, OR1A1, are also discussed. Other topics covered include the effects of nanoparticles and heavy metal toxicants on vertebrate and fish ORs, intranasal zinc products and the loss of smell (anosmia).